Peran Kepercayaan Merek Halal dalam Memediasi Pengaruh Religiusitas Islam terhadap Niat Pembelian Kosmetik Halal - Asbaruna, Latifah Wulandari (Ma'soem University, 2025)
The halal cosmetics industry in Indonesia has experienced rapid growth in line with the increasing awareness of Muslim consumers regarding the halal status of the products they use. Despite the availability of halal regulations and certification, psychological factors such as halal brand trust and consumer religiosity remain key determinants in shaping purchase intention. Previous studies have mostly examined the direct effect of religiosity on purchase intention, but few have explored the mediating role of halal brand trust, particularly in the context of cosmetic products. This study aims to analyze the mediating role of halal brand trust in the relationship between Islamic religiosity and purchase intention for halal cosmetics. A quantitative research method was employed, using a survey questionnaire distributed to 250 Muslim respondents in urban areas of Indonesia. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS software. The findings reveal that Islamic religiosity has a significant positive effect on purchase intention, both directly and through the mediation of halal brand trust. This mediating variable strengthens the relationship, highlighting the importance of halal brand strategies in enhancing Muslim consumer loyalty. Theoretically, this research enriches the halal marketing literature by positioning halal brand trust as a psychological mechanism bridging religious values with purchasing behavior. Practically, the findings provide guidance for halal cosmetic industry players to prioritize strengthening brand image and trust to increase purchase intention.